The immunome and embryo quality in sea bream and sea bass - Li, Lisen (2023)
Gilthead sea bream (Sparus aurata) and European sea bass (Dicentrarchus labrax) are teleosts belonging to Eupercaria and are the most important aquaculture fish species in the Mediterranean region. These two species are ranked second after the Atlantic salmon (Salmo salar) in production volume and value in the European Union (EU) aquaculture sector. Unpredictable fertilized egg/embryo quality and performance remain a bottleneck that threatens sustainability of sea bream and sea bass aquaculture, impeding the increased productivity of aquaculture that entirely depends on hatchery production. To address this issue, criteria and molecular markers linked to embryo quality that could be used to monitor and manage hatchery production were procured. Comparative molecular approaches using molecular biology, proteomics and transcriptomics were performed to analyze embryo performance and immunity in samples from several European commercial hatcheries. The core achievements were the: a) identification and characterization of lysozyme and complement 5 (C5) gene families and embryo and larval gene expression and enzyme activity from a diversity of hatcheries, b) characterization of the embryo proteome from three Mediterranean fish species [white sea bream (Diplodus sargus), meagre (Argyrosomus regius) and sea bream] 24h before hatch and at hatch and identification of common and species specific molecular patterns linked to biological function and putative quality-related proteins, c) comparative transcriptomics of good and poor quality sea bream embryos from several Mediterranean hatcheries. Qualitylinked transcripts and some elements of the regulatory epitranscriptome (non-coding RNA) were identified as well as the contribution of maternal proteins to embryos. Taken together, the results provide a comprehensive description of the molecular basis of sea bream and sea bass embryo development and reveal that immune-related molecules in fertilized eggs are low abundance. The development (quality)-related candidate markers ...